2001
DOI: 10.4049/jimmunol.166.11.6742
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ-Retinoid X Receptor Agonists Increase CD36-Dependent Phagocytosis ofPlasmodium falciparum-Parasitized Erythrocytes and Decrease Malaria-Induced TNF-α Secretion by Monocytes/Macrophages

Abstract: Severe and fatal malaria is associated with the failure of host defenses to control parasite replication, excessive secretion of proinflammatory cytokines such as TNF-α, and sequestration of parasitized erythrocytes (PEs) in vital organs. The identification of CD36 as a major sequestration receptor has led to the assumption that it contributes to the pathophysiology of severe malaria and has prompted the development of antiadherence therapies to disrupt the CD36-PE interaction. This concept has been challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
101
2
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 69 publications
(57 reference statements)
11
101
2
5
Order By: Relevance
“…Interestingly, it was also observed in this clinical trial that the administration of Rosiglitazone led to lower parasite clearance time 145. This observation might be explained from another study, which showed that Rosiglitazone preferentially increases the expression of CD36 on macrophages146 with minimal effect on endothelial cells148 and this would potentially lead to increased phagocytosis by these cells 149. Taken together, this study shows that targeting inflammatory responses at higher exposures might indeed be protective, but these processes need to be adequately investigated.…”
Section: Taking Advantage Of Immune Regulationsupporting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, it was also observed in this clinical trial that the administration of Rosiglitazone led to lower parasite clearance time 145. This observation might be explained from another study, which showed that Rosiglitazone preferentially increases the expression of CD36 on macrophages146 with minimal effect on endothelial cells148 and this would potentially lead to increased phagocytosis by these cells 149. Taken together, this study shows that targeting inflammatory responses at higher exposures might indeed be protective, but these processes need to be adequately investigated.…”
Section: Taking Advantage Of Immune Regulationsupporting
confidence: 61%
“…The molecular mechanism(s) that explain(s) how this compound down‐modulates the release of proinflammatory mediators is yet to be deciphered; however, it is known that Rosiglitazone regulates Toll‐like receptor (TLR) signalling in immune cells,146 and controls (increases) the expression of CD36 in innate immune cells146 via cross‐regulation147; therefore, this might provide insights to how Rosiglitazone modulates the proinflammatory responses in immune cells. Interestingly, it was also observed in this clinical trial that the administration of Rosiglitazone led to lower parasite clearance time 145.…”
Section: Taking Advantage Of Immune Regulationmentioning
confidence: 99%
“…Support for this hypothesis came from the fact that previous studies have demonstrated that the phagocytosis of P. falciparum-parasitized erythrocytes is enhanced by PPARc ligands without TNF-a production [11]. In addition, it has previously been shown that Th2 cytokines like IL-4 activate PPARc in Mu [18] while this cytokine down-regulates TLR2 expression [42], suggesting that TLR2 and PPARc are opposite signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all these results suggest that CD36 could be considered as functioning in an analogous way to CD14, which concentrates the LPS signal for transduction through TLR4 [40]. On the contrary, CD36 also has an established role in the phagocytosis of endogenous ligands (such as apoptotic cells) [41] or with P. falciparum, without enhancing proinflammatory signaling [10,11]. These data suggest that, depending on the ligands and the environment, CD36 could enhance different mechanisms to favor immune response activation or to eliminate endogenous ligands without inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation